Advanced maternal age pregnancy and its adverse obstetrical and perinatal outcomes in Ayder comprehensive specialized hospital, Northern Ethiopia, 2017: a comparative cross-sectional study - Mihret-ab Mehari; Hayat Maeruf; Carmen C. Robles; Solomon Woldemariam; Tesfay Adhena; Mussie Mulugeta; Abera Haftu; Hadgay Hagose; Henok Kumsa (BMC, 2020)
Abstract Background Advanced maternal age generally denotes age after 35 years during the time of delivery. Despite the fact that being pregnant at any reproductive age is not risk-free, older gravidity usually culminates with adverse outcomes both to the mother and fetus or neonate. This study aimed to determine the association of adverse obstetrical and perinatal outcomes with advanced maternal age pregnancy. The study was conducted in Ayder comprehensive specialized hospital, north Ethiopia, from 2015 to 2017. Methods chart review comparative cross-sectional study was employed. Data were retrieved from medical charts of 752 pregnant mothers (376 each for both the study;> 35-year-old and reference group;20-34 year old). Data was collected using a pretested and structured checklist using systematic sampling and data was entered & analyzed using SPSS version 20. Binary and multivariable logistic regression was run to determine the association of independent variables with dependent variables. Results This study revealed that advanced maternal age pregnancy was significantly associated with pregnancy induced hypertension [AOR 4.15, 95% CI (2.272-7.575), p <  0.001], ante partum hemorrhage [AOR 2.54, 95% CI (1.32-4.91), P = 0.005] & cesarean delivery [AOR 2.722, 95% CI (1.777-4.170), p <  0.001]. Furthermore, advanced maternal age pregnancy was also increasingly associated with adverse perinatal outcomes like preterm delivery [AOR 3.622, 95% CI (1.469-8.930), p = 0.005], low birth weight [AOR 3.137, 95% CI (1.324-7.433), p = 0.009], perinatal death [AOR 2.54, 95% CI (1.141-5.635), p = 0.022] and low fifth minute APGAR score [AOR 7.507, 95% CI (3.134-17.98), p <  0.001]. Notwithstanding this, maternal age was not found to be associated with amniotic fluid disturbances, premature rupture of membranes and post-term pregnancy. Conclusions Advanced maternal age is markedly linked with adverse obstetrical and perinatal outcomes. Therefore, it is better for health care providers to counsel couples, who seek to have a child in their later ages, about the risks of advanced maternal age pregnancy. In addition, health care workers need to emphasize on how to improve advanced age mothers' health through the utilization of contraception to reduce pregnancy in this age group.